Atopic dermatitis and risk of autoimmune diseases: a systematic review and meta-analysis - Wang, Hongli; Chen, Min; Wang, Tengyue; Cai, Wenyu; Li, Xuanlin; Huang, Lin; Wang, Mingzhu (Frontiers in Immunology, 2025)
BackgroundAtopic dermatitis (AD) is a common recurrent chronic inflammatory skin disease, and there is increasing evidence of a possible association between AD and autoimmune diseases.ObjectivesThis study aimed to summarize existing epidemiological studies on the association between AD and autoimmune diseases and to perform a meta-analysis of combinable results.MethodsWe conducted a thorough search for cohort studies, case-control studies and cross-sectional studies across the PubMed, Cochrane Library, and Embase databases, from their inception to May 24, 2024, using medical subject headings and relevant keywords. All data were meticulously analyzed using Stata statistical software version 17.0. The protocol was registered on PROSPERO (CRD42024547282).ResultA total of 26 cohort studies, comprising 1,629,723 patients with atopic dermatitis and 15,106,889 control subjects, were included in this meta-analysis. These studies were published between 2014 and 2024 and included 19 cohort studies, 2 case-control studies, and 5 cross-sectional studies. The current study demonstrated a significant association of atopic dermatitis with autoimmune diseases[HR 1.49, 95% CI (1.31-1.70); P<0.001], including celiac disease, systemic lupus erythematosus, Sjogren’s syndrome, ankylosing spondylitis, alopecia areata, rheumatoid arthritis, vitiligo, thyroid dysfunction, ulcerative colitis.ConclusionThe results of our study indicate a clear association between atopic dermatitis and autoimmune diseases, both in adults and children. Additionally, women were more likely to have autoimmune disease complications than men. However, due to the limited number of participants in our study, further research is needed to thoroughly investigate the relationship.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024547282.